Creation and Chaos in the Primeval Era and the Eschaton: A Religio-Historical Study of Genesis 1 and Revelation 12. By Hermann Gunkel - Nicholson, Ernest (The journal of theological studies, 2008)
Hermann Gunkel was a prime shaper of twentieth-century Old Testament research—perhaps, indeed, the pre-eminent influence. He pioneered the methods of form criticism and traditio-historical investigation in many shorter publications as well as in books, but the duo of works constituted by this volume, originally published in 1895 (an English translation of which is all the more welcome for being very long overdue), and his commentary on Genesis, first published in 1901, which has now also been translated, richly merit and will continue to warrant the description ‘classic’ in the history of research.